p38 mediates mechanical allodynia in a mouse model of type 2 diabetes - Hong Yu; Hayes John M; Oh Sang; Dauch Jacqueline R; Cheng Hsinlin T; Feldman Eva L (SAGE Publishing, 2010)
Abstract Background Painful Diabetic Neuropathy (PDN) affects more than 25% of patients with type 2 diabetes; however, the pathogenesis remains unclear due to lack of knowledge of the molecular mechanisms leading to PDN. In our current study, we use an animal model of type 2 diabetes in order to understand the roles of p38 in PDN. Previously, we have demonstrated that the C57BLK db/db (db/db) mouse, a model of type 2 diabetes that carries the loss-of-function leptin receptor mutant, develops mechanical allodynia in the hind paws during the early stage (6-12 wk of age) of diabetes. Using this timeline of PDN, we can investigate the signaling mechanisms underlying mechanical allodynia in the db/db mouse. Results We studied the role of p38 in lumbar dorsal root ganglia (LDRG) during the development of mechanical allodynia in db/db mice. p38 phosphorylation was detected by immunoblots at the early stage of mechanical allodynia in LDRG of diabetic mice. Phosphorylated p38 (pp38) immunoreactivity was detected mostly in the small- to medium-sized LDRG neurons during the time period of mechanical allodynia. Treatment with an antibody against nerve growth factor (NGF) significantly inhibited p38 phosphorylation in LDRG of diabetic mice. In addition, we detected higher levels of inflammatory mediators, including cyclooxygenase (COX) 2, inducible nitric oxide synthases (iNOS), and tumor necrosis factor (TNF)-α in LDRG neurons of db/db mice compared to non-diabetic db+ mice. Intrathecal delivery of SB203580, a p38 inhibitor, significantly inhibited the development of mechanical allodynia and the upregulation of COX2, iNOS and TNF-α. Conclusions Our findings suggest that NGF activated-p38 phosphorylation mediates mechanical allodynia in the db/db mouse by upregulation of multiple inflammatory mediators in LDRG.